PENGARUH STRUKTUR KEPEMILIKAN PERUSAHAAN DAN FEE AUDIT TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2017-2019) - Muhammad Ilham Utama; Totok Dewayanto (Diponegoro Journal of Accounting, 2021)
The aim of this study is to examine the role of audit fee and ownership structure which include managerial ownership, foreign ownership, principal-principal conflicts, on earnings management. The population in this study consists of manufacturing companies in Indonesia Stock Exchange for the period 2017 - 2019. Sample determined with purposive sampling method. Total sample of this research are 190 companies. This study used multiple regression analysis for hypotheses testing. The results of this study shows that managerial ownership, foreign ownership, and fee audit has negative and significant effect on earnings management. This study also shown that principal-principal conflict has insignificant effect on earnings management.